After Nehru, What? Britain, the United States, and the Other Transfer of Power in India, 1960–64 - McGarr, Paul M. (Taylor & Francis (Routledge), 2011)
In November 1959, India's Prime Minister, Jawaharlal Nehru, turned seventy. Having led his country since Britain's departure from South Asia in August 1947, Nehru's seventieth birthday stimulated debates, both inside and outside the Indian subcontinent, on India's future in a post-Nehruvian world. In the early 1960s, with the Indian premier's health deteriorating and Sino-Indian relations under strain, British and US policymakers evidenced increasing concern with whom, or perhaps more pertinently, with what, forces would govern the world's largest democracy after Nehru. This article, which draws upon recently released British and US archival records, provides the first assessment of Western involvement in the struggle to succeed Nehru which occurred within India's ruling Congress Party between 1960 and 1964. Moreover, it offers insights into Anglo-American concern that Nehru's health adversely affected Indian policymaking; the involvement of foreign intelligence services in India's domestic politics; and the misplaced expectations of British and US officials that the appointment of Lal Bahadur Shastri as India's second Prime Minister, in May 1964, would herald the beginning of a new and more productive relationship between India and the West.